Elastic torsional wave and corresponding nonlinear wave equation - Rushchitsky, J.J. (Reports of the National Academy of Sciences of Ukraine, 2022)
The new nonlinear wave equation describing the propagation of a torsional wave as one type of the elastic cylindrical waves is proposed. This equation is obtained using the tools of the nonlinear theory of elasticity within the framework of the five-constant Murnaghan’s model. In additopn to the classical linear summands, it contains the only cubically nonlinear ones. Some specifiсities of the derived equation are commented.